2013
DOI: 10.1093/nar/gkt1041
|View full text |Cite
|
Sign up to set email alerts
|

ESET methylates UBF at K232/254 and regulates nucleolar heterochromatin plasticity and rDNA transcription

Abstract: The remodeling of chromatin in the nucleolus is important for the control of ribosomal DNA (rDNA) transcription and ribosome biogenesis. Herein, we found that upstream binding factor (UBF) interacts with ESET, a histone H3K9 methyltransferase and is trimethylated at Lys (K) 232/254 by ESET. UBF trimethylation leads to nucleolar chromatin condensation and decreased rDNA transcriptional activity. UBF mutations at K232/254A and K232/254R restored rDNA transcriptional activity in response to ESET. Both ESET-ΔSET m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…Several studies have identified Setdb1 in the cytoplasm [ 19 ] and its cytoplasmic methyltransferase activity was demonstrated both in mammals [ 46 ] and C. elegans [ 47 ]. Furthermore, Setdb1 binds several non-histone proteins in the nucleus [ 22 , 67 ] and can also methylate some of them [ 68 , 69 ]. It is tempting to speculate that the relocalisation of Setdb1 to the cytoplasm could also lead to methylation of non-histone proteins in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified Setdb1 in the cytoplasm [ 19 ] and its cytoplasmic methyltransferase activity was demonstrated both in mammals [ 46 ] and C. elegans [ 47 ]. Furthermore, Setdb1 binds several non-histone proteins in the nucleus [ 22 , 67 ] and can also methylate some of them [ 68 , 69 ]. It is tempting to speculate that the relocalisation of Setdb1 to the cytoplasm could also lead to methylation of non-histone proteins in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…AGO2 is present in both the cytoplasm and the nucleus ( 65 ). SETDB1 functions mainly in the nucleus but can also localize in the cytoplasm, depending on the type of cells ( 51 , 66 ). As shown in Figure 3D , AR agRNA-bound AGO2 was localized at the promoter even in the absence of SETDB1 with AGO2 alone remaining and the AR promoter still active (Figure 1C ), suggesting that AGO2 arrives first and then recruits nuclear SETDB1.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas SUV39H1 is targeted to rDNA genes (together with sirtuin 1, as part of the energy-dependent nucleolar silencing complex) to methylate H3K9 (REF. 78), SETDB1 negatively regulates rDNA transcription by methylating one of the major nucleolar transcription factors, upstream-binding factor 1 (UBF1; also known as nucleolar transcription factor 1) 104 .…”
Section: Gene Silencingmentioning
confidence: 99%